(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2019)
The religiosity of Poles has been undergoing a far-reaching transformation for several years. All the research shows that less than half of the Polish society could be described as “the believers – practitioners”. The vast majority of Poles are people whose faith has individualized and is not strongly associated with the institution of the Catholic Church. In addition – as indicated by the described research – the moral assessment of another person is not related to the fact of his religiousness. The people live – to use Weber’s terms – in the disenchanted world in which they do not need clerics as interpreters of the reality.